2012
DOI: 10.1016/j.juro.2011.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Kidney Function and Stone Recurrence Rate After Percutaneous Nephrolithotomy for Staghorn Calculi: Outcomes of a Long-Term Followup

Abstract: In almost 80% of patients with staghorn stones renal function was improved or maintained after percutaneous nephrolithotomy, as documented during long-term followup. Stones recurred in a third of the patients with staghorn calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…[1] In a study by Akman et al [4] a total of 77 complications were observed in 64 patients. The most frequently seen complication was bleeding, and angioembolization was performed in 2 out of 47 patients because of development of pseudoaneurysm, and arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…[1] In a study by Akman et al [4] a total of 77 complications were observed in 64 patients. The most frequently seen complication was bleeding, and angioembolization was performed in 2 out of 47 patients because of development of pseudoaneurysm, and arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 98%
“…[6] Increased number or dimensions of stones bring with them more frequent interventions, Kaya et al The outcome of percutaneous nephrolithotomy on ≥50 mm staghorn and multiple calyceal stones higher number of complications, and lower stone-free rates. In a study by Akman et al [4] PNL was performed on 272 renal units because of the presence of staghorn kidney stone, and median stone-free rate at a single session was reported as 76.5%. More than one accesses were made into 102 (37.5%) units, while only a single access was made for 170 (62.5%) units.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have assessed the impact of PNL on renal function [25][26][27][28][29][30][31][32] . Usually there is an immediate decrease on renal function after surgery with return to baseline on long term.…”
Section: Vs Anatrophic Nephrolithotomymentioning
confidence: 99%